Review of the application of “3S” technique in environment quality assessment - WANG Wei-wu; WANG Ren-chao; ZHU Li-zhong (浙江大学学报. 农业与生命科学版)
The basic contents and types of environment quality assessment, the application of “3S” technology in environment quality assessment and disadvantage of the application were remarked in detail. Finally, the paper disscussed the way and studied fields of the further application of “3S” technique in environment quality assessment, and focus on espeacially the foreground of hyperspectral remote sensing and data technique such as data mining (DM) and data fusion in environment quality assessment.